2020
DOI: 10.4103/jpbs.jpbs_122_20
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of an integrated apex locator in determining working length in various irrigating solutions: An in vivo study

Abstract: A BSTRACT Objective(s): The objective of this in vivo study was to compare and evaluate the accuracy of VDW Gold (VDW, Munich, Germany) integrated apex locator (IAL) and Root ZX Mini (J. Morita Corp., Kyoto, Japan) in two different irrigating solutions. Materials and Methods: Forty patients who required extraction were included in the study. Following local anesthesia, access opening was performed under rubber dam is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 31 publications
2
7
0
1
Order By: Relevance
“…This study showed a higher but not statistically significant rate of acceptable results (100%, ±1 mm) in the saline and NaOCl groups, which is in agreement with previous studies 25,42 . In a recent study by Chukka RR 44 , NaOCl does not affect the WL determination of the EAL, similar with the present findings. HEBP's overestimated measurements in detecting AC can be explained by the fact that HEBP's ionization degree in liquids is lower than that of the other three solutions 45 .…”
Section: Discussionsupporting
confidence: 93%
“…This study showed a higher but not statistically significant rate of acceptable results (100%, ±1 mm) in the saline and NaOCl groups, which is in agreement with previous studies 25,42 . In a recent study by Chukka RR 44 , NaOCl does not affect the WL determination of the EAL, similar with the present findings. HEBP's overestimated measurements in detecting AC can be explained by the fact that HEBP's ionization degree in liquids is lower than that of the other three solutions 45 .…”
Section: Discussionsupporting
confidence: 93%
“…Nevertheless, majority of measurements obtained by the three devices, with both irrigating solutions did not surpass the apical foramen. These results are similar to that found in other studies which showed that the using EALs to determine the major foramen, in 0.0 EAL's mark led to overestimation of the working length (Connert et al 2018;Chukka et al 2020).…”
Section: Discussionsupporting
confidence: 91%
“…Future studies should evaluate other endodontic conditions, as foramen diameter, perforations, root resorptions, file diameter and others that may affect the performance of EALs, because in vivo situations differ from those found in controlled in vitro and ex vivo studies (Duran-Sindreu et al 2012Chukka et al 2020.…”
Section: Discussionmentioning
confidence: 99%
“…During RCP, 2.5% NaOCl is one of the most frequently used root canal irrigation solutions. Several studies have reported that NaOCl did not affect the determination of working length using EALs [18,23]. Thus, we used 2.5% NaOCl as the root canal irrigant in the present study.…”
Section: Discussionmentioning
confidence: 99%